Money and Exchange Mechanisms in the Near East. Some Introductory Remarks - Jankowska, Aleksandra (Acta Archaeologica Lodziensia, 2019)
The role and use of metals, and in particular silver, and the possible adoption of standardized pieces of silver as a pre-monetary form of money in exchange processes in the Near East, is a part of the debate on the existence of a market economy in the region. Silver seems to be used as a medium of exchange, a means of storing value, or as reference point for value. It is crucial in the context of interaction and exchange. Subsequently, a preference for silver could have spread throughout a wider area than in the eastern Mediterranean. However, silver in the Near East was never coined, it was weighed out at each transaction, and all silver was of equal value. Variability in the quality of the silver makes its analysis necessary, and indeed crucial, but sometimes it proves to be impossible to find evidence for this.